Star performers, unit performance and unit turnover: A constructive replication. (4th January 2021) - Taylor, Erik C.; Bendickson, Joshua S.
Abstract: In this constructive replication, we evaluate the effect of star performers on unit performance beyond the presence of other high performers and high mean levels of unit performance to clarify and confirm stars' unique contribution to unit performance. Furthermore, we extend prior work by assessing stars' moderating effect on the unit turnover‐to‐unit performance relationship. With a sample drawn from Major League Baseball, we confirm that stars have a positive influence on unit performance above and beyond the effects of high levels of mean unit productivity and other high performers, but that the strength of this relationship diminishes as the number of stars increases. We also find that stars moderate the relationship between unit turnover and performance such that star performers effectively eliminate the harmful effects of turnover on unit performance. However, this moderating effect is itself eliminated when the turnover rate changes drastically.